The Conflict of the Faculties Perspectives on Artistic Research and Academia - Borgdorff, Henk (Leiden University Press, 2012)
Artistic research is an endeavour in which the artistic and the academic are connected. In this emerging field of research artistic practices contribute as research to what we know and understand, and academia opens its mind to forms of knowledge and understanding that are entwined with artistic practices. Henk Borgdorff also addresses how we comment on such issues, and how the things we say cause the practices involved to manifest themselves in specific ways, while also setting them into motion. In this sense, this work not only explores the phenomenon of artistic research in relation to academia, but it also engages with that relationship.